Pengaruh Lingkungan Kerja dan Insentif Terhadap Kinerja Mitra Transportasi Online Grabcar di DKI Jakarta - Ivan Masdur; Ferryal Abadi (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
This study aims to determine whether there is an influence between the work environment and incentives on the performance of Grabcar partners operating in the DKI Jakarta area. The data collection technique used was census by distributing questionnaires to 100 Grabcar partners in the municipality of Jakarta. This study uses primary data obtained from questionnaire data and the analysis technique used is a simple regression analysis technique. The results of this study indicate that the work environment and incentives affect the performance of Grabcar partners operating in DKI Jakarta.Therefore the advice given to improve partner performance, Grab managers must pay more attention to the needs and complaints of partners.